No change in interictal C-reactive protein levels in individuals with episodic and chronic migraine: A case-control study and literature review - Park, Chae Gyu; Lee, Sue Hyun; Chu, Min Kyung (Frontiers in Neurology, 2022)
Objectives: The levels of some migraine biomarkers differ between episodic migraine (EM) and chronic migraine (CM), but information on C-reactive protein (CRP) levels in EM and CM is conflicting. Thus, this study aimed to evaluate CRP levels in participants with EM and CM in comparison to those in healthy controls. Methods: Plasma CRP levels were evaluated by high-sensitivity CRP tests in female participants with EM (n=174) and CM (n=191) and in healthy controls (n=50). Results: The results showed no significant difference in CRP levels among the EM, CM, and control groups (median and interquartile range, 0.40 [0.15–0.70] mg/L vs. 0.40 [0.15–1.00] mg/L vs. 0.15 [0.15–0.90] mg/L, p=0.991). The ratio of individuals with elevated CRP levels (>3.0 mg/L) did not significantly differ among the EM, CM, and control groups (3.4% [6/174] vs. 2.1% [4/191] vs. 0.0% [0/50], p=0.876). Multivariable regression analyses revealed that CRP levels were not significantly associated with headache frequency per month (β=-0.076, p=0.238), severity of anxiety (Generalized Anxiety Disorder-7 score, β=0.143, p=0.886) and depression (Patient Health Questionnaire-9 score, β=0.143, p=0.886). Further, CRP levels did not significantly differ according to clinical characteristics, fibromyalgia, medication overuse, preventive treatment, and classes of preventive treatment medications. Among participants with body mass index ≥25 kg/m2, the CRP levels in EM (n=41) and CM (n=17) were numerically higher than those in the control (n=6) (1.30 [0.28–4.25] mg/L vs. 1.10 [0.50–3.15] mg/L vs. 0.40 [0.15–0.83] mg/L, p=0.249) but did not reach statistical significance. Conclusions: Interictal CRP level is not likely to be a biomarker for EM or CM.